Nutritional status and morbidity pattern among school children in an urban slum of Kolkata, India - Dan, Amitabha; Pasi, A. R.; S., Selvaganapathi; G. P., Maitreyee; Purkait, Prithu (International Journal Of Community Medicine And Public Health, 2023)
Background: Sickness and morbidity rates in Indian school going children are among the highest in the world. Poor health and sickness absenteeism results in school dropouts and it is more among the female children as compared to male children. Present study was conducted to study the nutritional status and morbidity pattern among children attending the school health clinics in an urban area of West Bengal India. Methods: A cross-sectional study was conducted in the field practice area of urban health centres (UHC) of AIIH and PH Kolkata, West Bengal. Children enrolled in class 1-10 were included in the study by using systematic random sampling technique. Data was collected by using semi-structured questionnaire, clinical history and physical examination was done. Results: Out of total 254 students, 129 (50.8%) were boys and 125 (49.2%) were girls. Dental caries and skin diseases like ringworm infection, cuts and fungal infection were most common types of morbidity found in school children. Dental caries and skin diseases both were more common in girls as compared to the boys. Underweight was found in more than 70% of the children and their BMI was significantly low as compare to the ICMR standard. Conclusions: The proportion of malnutrition is very high in the school children of the field practice area of UHC Chetla and there is need to create opportunities to increase the family income and awareness programme to increase the nutritive values of foods prepared at household level.